On oscillation free controller changes - Cunguara, Milton; Silva, Tomas; Pedreiras, Paulo (Systems & control letters, 2013)
Control systems are typically subject to strong, and often conflicting, constraints. One of the techniques that have been extensively investigated consists in using several controllers, designed to have different resource needs, and consequently, to exhibit different performance levels. These controllers are switched dynamically, to obtain the desired quality of control while using the lowest possible amount of resources. However, the research made so far has been essentially focused on the rules for triggering the controller switching, neglecting the full extent that such changes have in the system. In particular, switching controllers often causes output oscillations that may negate the potential performance gains. In this paper, firstly, the cause for oscillations in the presence of period changes is investigated. Then, it is presented a solution, based on a change of basis matrix. The experimental evaluation shows that important performance gains are achieved in key control performance indicators such as overshoot, settling time and error.